2014
DOI: 10.3168/jds.2013-7391
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dry period length and dietary energy source on energy balance, milk yield, and milk composition of dairy cows

Abstract: The objective of this study was to evaluate the effects of dry period length and dietary energy source in early lactation on milk production, feed intake, and energy balance (EB) of dairy cows. Holstein-Friesian dairy cows (60 primiparous and 108 multiparous) were randomly assigned to dry period lengths (0, 30, or 60 d) and early lactation ration (glucogenic or lipogenic), resulting in a 3 × 2 factorial design. Rations were isocaloric and equal in intestinal digestible protein. The experimental period lasted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
145
1
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(157 citation statements)
references
References 36 publications
8
145
1
3
Order By: Relevance
“…A similar result was also reported by van Knegsel et al . (), who found that dietary energy source (Lipogenic ration group vs. Glucogenic ration group) affects milk fat content (4.38% vs. 4.27%, P = 0.05). Moallem et al .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar result was also reported by van Knegsel et al . (), who found that dietary energy source (Lipogenic ration group vs. Glucogenic ration group) affects milk fat content (4.38% vs. 4.27%, P = 0.05). Moallem et al .…”
Section: Discussionmentioning
confidence: 97%
“…However, few studies concerning net energy requirement and energy partitioning of dairy cows under heat stress has not been reported. Recent reports (Huang et al 2014;van Knegsel et al 2014) reflected that dietary energy content may affect energy metabolism of cows. Therefore, the objectives of the present study were to examine the effects of dietary energy concentration of Holstein cows in mid-lactation on milk yield, energy partitioning, efficiency of milk yield, and net energy requirements during medium heat load conditions by the combination of comprehensive experiments, regression analysis, and total collection plus gas exchange methods.…”
Section: Introductionmentioning
confidence: 99%
“…Materiaal en methode van dit experiment staat uitgebreid beschreven in het wetenschappelijk artikel (Van Knegsel et al, 2014a) en het WHYDRY rapport (Van Knegsel et al, 2014b …”
Section: Materiaal En Methodeunclassified
“…Unfortunately, Albornoz et al (2013) did not report papillae surface area, and the decrease in k a VFA might also be explained by a reduction in epithelial blood flow (discussed below). Finally, considering that the majority of papillae atrophy occurs during the first weeks of the dry period, it is unlikely that a shorter dry period (van Knegsel et al, 2014) than those in the present experiments will prevent such atrophy of the rumen papillae.…”
Section: Macroscopic Adaptation Of the Rumen Papillaementioning
confidence: 74%